Implementation and Analysis of WiFi Human Interface Device (HID) USB Using ATMEGA32U4 and ESP8266 - Gilang Ryan Fernandes; Ika Mei Lina (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2023)
Advances in technology have resulted in hacking occurring everywhere. Hacking is the act of illegally accessing data and information. It is not uncommon for many hacking cases to harm various parties due to ignorance. The results of hacking at this time are widespread, one of which is a ransomware virus that can encrypt data, a keylogger is software that can monitor keyboard activity, and a WiFi USB human interface device which is where this attack is a virtual keyboard. This research assembles the components used for Human Interface Device (HID) by utilizing ATMEGA32U4 as a virtual keyboard and ESP8266 as WiFi media. This technique is used to obtain target information and data. This research aims to make people more careful and overcome hacking. It is hoped that people will be more concerned about system and data security. Based on the research results, WiFi HID USB attacks can be dangerous for computer owners who need to be more aware of various hacker attacks because this technique can directly take target access.